2019
DOI: 10.1001/jamasurg.2018.3213
|View full text |Cite
|
Sign up to set email alerts
|

Association of Hospital Length of Stay and Complications With Readmission After Open Pancreaticoduodenectomy

Abstract: had full access to all the data in the study and take responsibility for the integrity of the data and the accuracy of the data analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 7 publications
2
14
0
2
Order By: Relevance
“…Specifically, while 30‐day mortality and unplanned 30‐day readmission were achieved over 90% of the time, avoiding a prolonged LOS was less common. In an evaluation of the National Surgical Quality Improvement Program (NSQIP) dataset, Jiang et al 25 noted that a LOS >8 days was associated with a higher rate of complications. Other investigators have similarly demonstrated that prolonged LOS following PD functioned as a strong surrogate of postoperative complications 22,26 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Specifically, while 30‐day mortality and unplanned 30‐day readmission were achieved over 90% of the time, avoiding a prolonged LOS was less common. In an evaluation of the National Surgical Quality Improvement Program (NSQIP) dataset, Jiang et al 25 noted that a LOS >8 days was associated with a higher rate of complications. Other investigators have similarly demonstrated that prolonged LOS following PD functioned as a strong surrogate of postoperative complications 22,26 .…”
Section: Discussionmentioning
confidence: 99%
“…Data on perioperative complications were not reported in the NCDB and therefore the incidence and severity of complications following PD could not be analyzed or included in the TOO definition. To account for this shortcoming, LOS, which has been demonstrated to correlate strongly with occurrence of in‐hospital complications, was included in the TOO definition 22,25,40 . In addition, other factors may have been included in the definition of TOO.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…піталізації, а відповідно й повторної операції, наркозу, післяопераційного періоду, що пов'язане з відповідними для цього ризиками та затратами. Відомо, що при збільшенні часу перебування хворого у стаціонарі з кожним днем збільшується ймовірність госпітальних інфекцій і інших ускладнень, пов'язаних з перебуванням на стаціонарному лікуванні та гіподинамією [4,14]. Також фіксується зростання смертності [21,2].…”
Section: результати обговоренняunclassified